2020
DOI: 10.1371/journal.pone.0233472
|View full text |Cite
|
Sign up to set email alerts
|

Work-related psychosocial risk factors and psychiatric disorders: A cross-sectional study in the French working population

Abstract: The study estimates the prevalence of probable psychiatric disorder in the working population, determines the proportion of people presenting a probable psychiatric disorder among people exposed to work-related psychosocial risk factors (PSRFs), and identifies which PSRF has the strongest association with having a probable psychiatric disorder. MethodsA cross-sectional study conducted in March 2018 involved a representative sample of the French working population. The General Health Questionnaire 28 (GHQ-28) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…These situations are likely to be stressful; thus, psychological disorders may increasingly be caused by work-related stressors ( 40 ). The job strain model (demand-control-support model) has already been confirmed in a large number of studies on employees in developed countries, and many psychosocial work factors have been linked to mental health problems ( 4 , 32 ). Recently, studies have suggested that other exposures may play a role in mental disorders (such as effort–reward imbalance and workplace bullying) ( 41 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These situations are likely to be stressful; thus, psychological disorders may increasingly be caused by work-related stressors ( 40 ). The job strain model (demand-control-support model) has already been confirmed in a large number of studies on employees in developed countries, and many psychosocial work factors have been linked to mental health problems ( 4 , 32 ). Recently, studies have suggested that other exposures may play a role in mental disorders (such as effort–reward imbalance and workplace bullying) ( 41 ).…”
Section: Discussionmentioning
confidence: 89%
“…It is reported that the global point prevalence of depression in the working population ranged from 3.73 to 19.0% ( 1 3 ). For anxiety, another prevalent mental health problem across the world, the prevalence of anxiety among the working population ranged from 5.40 to 20.70% ( 4 , 5 ). Previous studies have shown that mental health problems at work could reduce employees' work productivity and performance, could increase disability, could reduce quality of life, and may lead to premature early retirement, which results in direct social and economic costs ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present work was based on the analysis of a cross-sectional study conducted in March 2018 on a sample of 3200 workers, representative of the French working population, 12 the ‘Baromètre Travail et Santé Psychique’ survey. Representativeness was achieved by using both quota sampling for sex, age, occupation and residence locality, 12 and the rim weighting method (raking). 13 Workers were recruited in the ‘Ipsos Access Panel’ and were invited by email to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A 44-item questionnaire 12 was used to measure work-related WPSFs based on an integrative view of several conceptual models on WPSFs and their effects (Karasek, 3 Siegrist, 4 Greenberg 5 and Harvey et al 15 ). All these models describe the individual perception of the work environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation